2016
DOI: 10.1155/2016/8319287
|View full text |Cite
|
Sign up to set email alerts
|

Unique AGG Interruption in the CGG Repeats of the FMR1 Gene Exclusively Found in Asians Linked to a Specific SNP Haplotype

Abstract: Fragile X syndrome (FXS) is the most common inherited intellectual disability. It is caused by the occurrence of more than 200 pure CGG repeats in the FMR1 gene. Normal individuals have 6–54 CGG repeats with two or more stabilizing AGG interruptions occurring once every 9- or 10-CGG-repeat blocks in various populations. However, the unique (CGG)6AGG pattern, designated as 6A, has been exclusively reported in Asians. To examine the genetic background of AGG interruptions in the CGG repeats of the FMR1 gene, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, it has been found that increased instability seems to be correlated with the presence of the first interruption at the 10th triplet ( Gunter et al, 1998 ) and to the total number of AGGs. The loss of AGGs occurs in a polarized way at the 3′-end, creating a long pure (CGG)n with higher mutability ( Kunst and Warren, 1994 ; Limprasert et al, 2016 ). In the presented case, the allele was a pure stretch of CGG without any AGG interruption.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been found that increased instability seems to be correlated with the presence of the first interruption at the 10th triplet ( Gunter et al, 1998 ) and to the total number of AGGs. The loss of AGGs occurs in a polarized way at the 3′-end, creating a long pure (CGG)n with higher mutability ( Kunst and Warren, 1994 ; Limprasert et al, 2016 ). In the presented case, the allele was a pure stretch of CGG without any AGG interruption.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] The loss of AGGs occurs in a polarized way at the 3′-end, creating a long pure (CGG)n with higher mutability. 17,18 On the other hand, while analyzing the interspersion pattern of the repeat, an increased instability seems to be correlated with the presence of the first interruption at the tenth triplet, as the configuration (CGG)9AGG (CGG)n is frequently observed in large normal alleles. 19 In addition, normal-sized alleles with more than 24 pure CGGs at the 3′-end frequently share the typically studied DXS548-FRAXAC1 FXS haplotype, suggesting that these alleles could be more prone to expand.…”
Section: Introductionmentioning
confidence: 99%
“…Also Falik-Zaccai et al (1997) showed high prevalence of premutation and full mutation in the Tunisian ethnicity among the Jewish population, likely related to unique founder effect and genetic drift phenomena for accumulation of predisposed alleles in the population. Limprasert et al (2016) showed that specific haplotype were associated with the loss of AGG interruptions. Recently, Sun et al (2018) showed that disease-associated tandem repeats are located to TAD boundaries and affect their insulation.…”
Section: Al (mentioning
confidence: 99%
“…It has been demonstrated that, in addition to the CGG repeat number, increased instability correlates with AGG loss (Gunter et al, 1998;Nolin et al, 2015Nolin et al, , 2013Yrigollen et al, 2012Yrigollen et al, , 2014. The loss of AGG repeat occurs at the 3'end, creating a long pure (CGG)n stretch with higher mutability (Kunst & Warren, 1994;Limprasert, Thanakitgosate, Jaruthamsophon, & Sripo, 2016).…”
mentioning
confidence: 99%